"You bet she can fuck" - Trends in Female AI Narratives within Mainstream Cinema: Ex Machina and Her. - YEE, Sennah (Ekphrasis (2067-631X), 2017)
In today's digital age, we are becoming more like machines and machines are becoming more like us. Donna Haraway's seminal essay, "A Cyborg Manifesto," proposes the cyborg as a transgressive figure capable of subverting oppressive power structures. While there is no denying this powerful imagery, what are the common trends in female AI narratives in mainstream cinema? This paper examines the films Ex Machina (2015) and Her (2013), which both feature male human protagonists and female AIs (Ava, a feminized robot in Ex Machina and Samantha, a female operating system in Her). Ava's and Samantha's highly sexual yet innocent characterizations and similar desires for freedom are reflective of societal anxieties surrounding male control over female agency. As gendered AIs continue to populate our media, one can only hope that we can live up to Haraway's vision of the cyborg, and expand the scope of our questions and concepts past male pleasure and women as research-fetish objects.